PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI, DAN BUDAYA ORGANISASI TERHADAP KINERJA ASN PADA BALAI PERLUASAN KESEMPATAN PERLUASAN KESEMPATAN KERJA KENDARI KEMENTERIAN KETENAGAKERJAAN - Nirmayani Nirmayani; Abdul Razak; Ummy Kalsum; Andi Runis Makkulau (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The phenomenon that occurs in Center for Expansion of Kendari Employment Opportunities Ministery of Labour Opportunity Expansion employees at the Ministry of Manpower shows that performance is still not optimal and tends to decrease in carrying out their work in accordance with the demands of the work unit. This study aims to determine the effect of leadership style, communication, and organizational culture on employee performance at Center for Expansion of Kendari Employment Opportunities Ministery of Labour. This research is an explanatory research that studies the relationship between two or more variables, then attempts to explain the phenomena that occur. The results of the study show that: (1) Leadership Style, Communication and Organizational Culture simultaneously have a positive and significant effect on the performance Center for Expansion of Kendari Employment Opportunities Ministery of Labour. This means that improving Leadership Style, Communication, and Organizational Culture together will result in significant performance improvements for Center for Expansion of Kendari Employment Opportunities Ministery of Labour. (2) Leadership style has a negative but not significant effect on employee performance at Center for Expansion of Kendari Employment Opportunities Ministery of Labour This means that the decreasing Leadership Style will not affect employee performance. (3) Communication has a positive and significant influence on employee performance at Center for Expansion of Kendari Employment Opportunities Ministery of Labour (4) Organizational Culture has a positive but not significant influence on Center for Expansion of Kendari Employment Opportunities Ministery of Labour employee performance.”